If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -6x + 6 = 4x + -8 Reorder the terms: 6 + 6 + -6x = 4x + -8 Combine like terms: 6 + 6 = 12 12 + -6x = 4x + -8 Reorder the terms: 12 + -6x = -8 + 4x Solving 12 + -6x = -8 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 12 + -6x + -4x = -8 + 4x + -4x Combine like terms: -6x + -4x = -10x 12 + -10x = -8 + 4x + -4x Combine like terms: 4x + -4x = 0 12 + -10x = -8 + 0 12 + -10x = -8 Add '-12' to each side of the equation. 12 + -12 + -10x = -8 + -12 Combine like terms: 12 + -12 = 0 0 + -10x = -8 + -12 -10x = -8 + -12 Combine like terms: -8 + -12 = -20 -10x = -20 Divide each side by '-10'. x = 2 Simplifying x = 2
| 2x+4+2=48 | | 3(g-1)= | | X^2(x+2)-x(x+2)-6(x+2)= | | 0=4x^4-29x^2+7 | | 5h+3=2h-9 | | p(x)=4x^4-29x^2+7 | | X^4-17x^2+16= | | 2x^2+1x=21 | | 950.6664=4*3.14*r^2 | | 5y=135+9x | | 2x+7=2(3x-5) | | -2[5x-2-2(x+1)]=7x+7 | | 5x^3-100x=0 | | 7x+21=5 | | 7x-4=-3x+8 | | 5w-w+1=-10+w+23 | | 5.5x+13=62.5 | | 4l-12=68 | | 3(x+9)=2x-1 | | 3[-3x-2-2(x+1)]=7x+1 | | 4.74x+100=22.4676+10x | | -9x-2y=10 | | 8x-5y=-14 | | 3x+1-7(x+1)=6x+2 | | -1+3+-1-6=3(-1)-2 | | 3x^2-12=o | | -33+r=-54 | | 10x^3=40x^2 | | 4x^2-53=11 | | -3x+5ab=30 | | 3t+9-5= | | 4x^3-500=0 |